Development and validation of Cognitive Training Intervention for Alzheimer's disease (CTI-AD): A picture-based interventional program. (May 2020) - Bajpai, Swati; Tripathi, Manjari; Pandey, RM; Dey, A.B; Nehra, Ashima
Introduction: Alzheimer's disease is a gradual and progressive disorder which cripples the person's functionality due to cognitive decline. Many clinicopathological and pharmacological therapy has the potential to slow down the progression of the disease but has limited efficacy. One complimentary approach that has emerged is cognitive training interventions which have shown synergistic effect with the drug therapy. Nevertheless, many cognitive interventions lack on specificities of the intervention due to which its efficacy gets scrutinized. Objective: To describe the foundation, content, and development of Cognitive Training Intervention for Alzheimer's disease (CTI-AD) along with the treatment feasibility based on a pilot study. Materials and methods: A culture-specific picture-based eight weeks cognitive training manual was developed based on extensive review and focused group discussions. It was standardized on 63 older participants (48 healthy controls (HC); 15 early Alzheimer's disease cases). Results: All the tasks were progressive in nature and were found effective in discriminating the cognitive performance of early Alzheimer's disease and HC throughout the intervention period. Moreover, it also improved early Alzheimer's disease performance on the memory (HC: 1st week/8th week = 21.6 ± 5.7/57.3 ± 19.0; early Alzheimer's disease: 1st week/8th week = 48.5 ± 22.9/60.5 ± 21.8); attention (HC: 1st week/8th week = 90.2 ± 18.0/196.9 ± 28.0; early Alzheimer's disease: 1st week/8th week = 216.6 ± 78.2/286.8 ± 87.0) and language (HC: 1st week/8th week = 29.8 ± 9.4/115.3 ± 31.1; early Alzheimer's disease: 1st week/8th week = 211.8 ± 68.4/270.4 ± 104.9) domains, respectively, from the baseline level. Conclusion: The current manual (CTI-AD) is one of the first promising non-pharmacological program developed nationally with a strong theoretical base to cater to the tertiary needs of the older adults with early Alzheimer's disease.